COVID-19 pandemic and the social determinants of health - Meador, John E.; James, Wesley; Branson, Joseph; Bennett, Jonathan; Matthews, Karen (Frontiers in Epidemiology, 2023)
Hesitancy to receive a COVID-19 vaccination across sub-groups within the US population contributed to higher illness rates and deaths. Specifically, minority groups and those living in rural and remote areas are more vaccine-hesitant populations known to suffer from higher disparities in health. Identifying successful and replicable approaches to promoting vaccination within these subpopulations is critical to ensuring vaccination rates can be maximized in these vulnerable groups. In this paper, we present findings from the RIVERs project, a multi-state effort to spread accurate information related to COVID-19 vaccinations using a variety of community and media-based methods as well as provide vaccinations. Vaccination rates for Black people in Mississippi exceeded those of White people, likely due to the concerted effort of regional health and community organizations. Propensity score matching is performed to test intervention styles using spatial and temporal data related to approximately 7,000 events across Mississippi and parts of Tennessee and publicly available data on vaccination rates and socio-economic data. We demonstrate that vaccination rates within the vulnerable groups may be closely related to misinformation being spread through local social networks and that interventions carried out by local leaders with high levels of local social capital are best at quashing misinformation at the local level. We recommend that policymakers consider the importance of local efforts as an effective tool in increasing vaccination rates in future pandemics.